Multidisciplinary Design of Ultra-High-Speed Electrical Machines - Ismagilov, Flur R.; Uzhegov, Nikita; Vavilov, Vyacheslav E.; Bekuzin, Vladimir I.; Ayguzina, Valentina V. (IEEE transactions on energy conversion, 2018)
This paper presents a multidisciplinary design algorithm of the ultra-high-speed electrical machine (UHSEM). Presented algorithm enables UHSEM design with a rotational speed of 0.5-1.2 Mrpm, taking into account the mutual influence of thermal, mechanical, and electromagnetic processes. Based on the algorithm, the 138 W UHSEM with a 1.2 Mrpm rotational speed was calculated. Material selection for the active parts of the machine is described. Analysis of the suitable bearings for UHSEM application is presented. Mechanical, electromagnetic, and cooling design aspects are shown with example of the calculated machine. To evaluate the effectiveness of the developed computer models and the calculation method, the experimental model of the 100 W UHSEM was tested in the motor mode at the rotational speed of 500 000 rpm. The test results demonstrated that the multidisciplinary design algorithm has high accuracy and is suitable for UHSEMs. The discrepancy between developed models and experimental results does not exceed 7%.